Polyclonality among clinical strains of non-pigmented rapidly growing mycobacteria: phenotypic and genotypic differences and their potential implications. (April 2015) - García-Pedrazuela, M.; Frutos, J.M.; Muñoz-Egea, M.C.; Alcaide, F.; Tórtola, T.; Vitoria, A.; Cortés, P.; Esteban, J.
Abstract: To investigate the potential implications (especially the implications in clinical significance and antimicrobial susceptibility) of polyclonality among rapidly growing mycobacteria, we performed random amplified polymorphic DNA analysis in 64 clinical isolates of which the clinical significance was established. Phenotypic characteristics (antimicrobial susceptibility test, colony morphology and growth rate) of each clone were studied. Polyclonality was detected in 13 of the isolates (20.3%). There was a relationship between monoclonality and clinical significance (p 0.0096). Monoclonal and polyclonal isolates showed different behaviour in antimicrobial susceptibility. There was a strong relationship between monoclonality and those species that are more pathogenic for humans, and also with clinical significance of the isolates.